2017
DOI: 10.4172/2157-7587.1000264
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Participatory Evaluation of Chickpea Varieties in Mirab Badwacho and Damot Fullasa Districts of Southern Ethiopia

Abstract: Chickpea is one of the grain food legumes contributing an enormous amount of protein to the human diet in Southern Ethiopia. Though a lot of improved varieties were released by research centers farmers depend on low yield and local varieties. Hence, participatory variety selection is one of the methods used to evaluate varieties through involvement of users. Participatory Variety Selection (PVS) were conducted during 2015/2016 in Mirab Badwacho and Damot Fullasa districts of South region, Ethiopia to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…P 2 O 5 of 160 and 200 kg ha −1 had 5.91 (stem dry matter) and 2.71 t ha −1 (grain) yield, consecutively [126]. Such grain yield was considered high against other countries, such as India, Pakistan, and Ethiopia with mean yield of 0.91, 0.47, and 1.91 t ha −1 , sequentially [152,153].…”
Section: Effect Of P Application Rate On Nodulation Growth and Yield Performance Of Chickpeamentioning
confidence: 98%
“…P 2 O 5 of 160 and 200 kg ha −1 had 5.91 (stem dry matter) and 2.71 t ha −1 (grain) yield, consecutively [126]. Such grain yield was considered high against other countries, such as India, Pakistan, and Ethiopia with mean yield of 0.91, 0.47, and 1.91 t ha −1 , sequentially [152,153].…”
Section: Effect Of P Application Rate On Nodulation Growth and Yield Performance Of Chickpeamentioning
confidence: 98%
“…To improve the problem, participatory variety selection is the better option to fit the crop bring together of both target environments and user preferences. Participatory varietal selection is being conducted in many crops like chickpea, common bean, Bread wheat and Maize [4][5][6][7][8]. Danial et al [9] reported that farmer's selection criteria vary with environmental conditions, traits of interest, ease of cultural practice, processing, use and marketability of the product, ceremonial and religious values.…”
Section: Introductionmentioning
confidence: 99%
“…Chickpea varieties Yelibe and Fetenech showed the lowest (42 and 42) days to flowering and the shortest (96 and 109) days to maturity, respectively; whereas Ararti and Habru showed the highest (140 and 132) days to maturity, respectively. This variation might be due to the genetic variation as reported by Goa et al [14]; Alemu et al [9]; Gonzales and Gonzales [10].…”
Section: Growth and Yield Attributesmentioning
confidence: 80%
“…To fully exploited production potential, the varieties should be productive and match the growing conditions in the country. Several research findings [9][10][11][12][13][14] indicated that chickpea varieties produce significantly different yields at different locations emphasizing the need for their evaluation under various climatic and soil conditions. The participation of small-scale farmers is also limited during improved variety development.…”
Section: Introductionmentioning
confidence: 99%